2014
DOI: 10.1007/s13555-014-0057-y
|View full text |Cite
|
Sign up to set email alerts
|

Single Blinded Left-to-Right Comparison Study of Excimer Laser Versus Pulsed Dye Laser for the Treatment of Nail Psoriasis

Abstract: IntroductionNail psoriasis is relatively difficult to treat. Excimer laser has been approved for the treatment of psoriasis since 2000. Pulsed dye laser (PDL) in psoriasis therapy has shown good response rates, with extended remissions. This is the first study assessing both the excimer and PDL lasers in nail psoriasis.MethodsIn a comparison study, excimer laser versus PDL for the treatment of nail psoriasis was evaluated in 42 patients. The right hand nails were treated with excimer laser twice weekly and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 29 publications
2
21
0
3
Order By: Relevance
“…Although the application parameters of the 595-nm PDL were in part comparable with that of prior studies, [4][5][6][7][8][9] we observed a disparity in effectiveness that could be attributed to fewer sessions or non-use of concomitant therapy in our cohort.…”
supporting
confidence: 79%
“…Although the application parameters of the 595-nm PDL were in part comparable with that of prior studies, [4][5][6][7][8][9] we observed a disparity in effectiveness that could be attributed to fewer sessions or non-use of concomitant therapy in our cohort.…”
supporting
confidence: 79%
“…Another option for nail psoriasis is intralesional steroid‐injection therapy, which is limited by the pain of injection; however, recent data from a small ( N = 17) prospective trial suggested high efficacy for novel administration via needle‐free jet injector (Nantel‐Battista, Richer, Marcil, & Benohanian, ). Laser therapy can also be considered for patients with nail psoriasis and in a single blinded left‐to‐right comparison study ( N = 42), treatment with pulsed‐dye laser was significantly more effective than excimer laser (Al‐Mutairi, Noor, & Al‐Haddad, ). Additionally, the efficacies of pulsed‐dye laser and neodymium‐doped yttrium aluminum garnet (Nd:YAG) laser are comparable, but Nd:YAG laser therapy is more painful (Arango‐Duque, Roncero‐Riesco, Usero Bárcena, Palacios Álvarez, & Fernández López, ).…”
Section: Methodsmentioning
confidence: 99%
“…Parameters of PDL were 8-10 J/cm 2 , pulse lenght of 30 nm and a 7 mm spot. In case of excimer laser the procedure was started from 2 × MED (minimal erythema dose) with subsequent uptitration of the dose by 200 mJ per session, up to 5000 mJ/cm 2 [30]. Authors suggest that the achieved effect could be a result of poor UVB penetration in the nail plate [31].…”
Section: Excimer Lasermentioning
confidence: 99%
“…For that reason a topical pharmacotherapy of nail psoriasis will be used for a long time, particularly in cases of low advancement of the disease. o 200 mJ co sesję do 5000 mJ/cm 2 [30]. Autorzy sugerują, że osiągnięty efekt może być wynikiem słabej penetracji UVB przez płytkę paznokciową [31].…”
Section: Laser Ekscymerowyunclassified